PENGGUNAAN KONJUNGSI PADA TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 22 KERINCI - Venda Mentilia; Emidar (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The first aim of this research is, this research aims to explain the types of conjunctions used in descriptive texts written by students in class VII of SMP Negeri 22 Kerinci. Second, this research explains how conjunctions are used in student description texts in class VII of SMP Negeri 22 Kerinci. This research is qualitative and uses a descriptive approach. This research was conducted at SMP Negeri 22 Kerinci. The data used in this research came from text descriptions of class VII students at the school. The descriptive text used in this research is the descriptive text of class VII students at the school. Classifying, analyzing, and discussing data is used to analyze it. The results of the research show that in the descriptive text of class VII students at SMP Negeri 22 Kerinci there are three types of conjunctions: 124 coordinating conjunctions, 186 subordinating conjunctions, and 2 inter-sentential conjunctions. The second type of conjunction used in the descriptive text of class VII students at SMP Negeri 22 Kerinci is 80 correct coordinating conjunctions. There are 89 correct subordinating conjunctions and 2 inter-sentential conjunctions. There are also 44 incorrect coordinating conjunctions and 97 incorrect subordinating conjunctions.